Analisis kesalahan siswa dalam memecahkan masalah soal cerita matematika materi kecepatan, jarak, dan waktu berdasarkan kecerdasan logis matematis di sekolah dasar - Novita Dwi Ashohib; Riyadi Riyadi; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2022)
This research aims to describe and find out the causes of errors made by students in solving mathematical problems in the form of story questions with speed, distance, and time material based on the level of logical mathematical intelligence. This research is a qualitative descriptive study with a case study approach. The data sources of this research include the results of the logical-mathematical intelligence test, the results of the speed, distance, and time story test results, the results of student interviews, and the results of classroom teacher interviews. The sampling technique was done by purposive sampling. Data was collected by using test and interview techniques. Test the validity of the data using triangulation techniques. The results showed that students who had high logical mathematical intelligence made mistakes in carrying out the completion plan according to Polya's steps. Students with logical-mathematical intelligence are making mistakes in formulating plans, carrying out completion plans and re-checking answers. Students who have low logical-mathematical intelligence make more mistakes in understanding the problem, compiling a settlement plan, implementing a settlement plan, and re-examining the answers according to Polya's steps. The causes of errors made by students are that students have not mastered multiplication and division, students have not fully understood the material, and students tend to be unfamiliar with re-examining answers.